In-situ growth of bimetallic sulfide NiCo2S4 nanowire on carbon cloth for asymmetric flexible supercapacitors. (October 2021) - Liang, Xiaoyuan; He, Hang; Yang, Xijia; Lü, Wei; Wang, Liying; Li, Xuesong
Highlights: Needle-like NiCo2 S4 nanowire on activated carbon cloth were successfully prepared. No conductive additives and adhesives are required, which further reduces the mass load of the device. NiCo2 S4 @CC has the largest specific capacitance of 1568.8 mF cm -2 at 1 mA cm -2 . The asymmetric flexible supercapacitor displays high energy density (93.43 µWh cm -2 ). Abstract: Fully flexible, lightweight, and high-performance supercapacitor was designed, with in-situ grown NiCo2 S4 nanowire on activated carbon cloth (CC) by a simple two-step hydrothermal method. Needle-like NiCo2 S4 nanowire uniformly arranged on CC substrate, not only increases the sufficient contact area between the electrode and the electrolyte, but also favor rapid electron transfer. Benefitting from these advantages, this designed NiCo2 S4 @CC electrode expresses high area capacitance of 1568.8 mF cm −2 at 1 mA cm −2 and good capacitance retention with 9.9% capacitance lost after 10000 cycles. Moreover, a flexible asymmetric supercapacitor using NiCo2 S4 @CC as the anode and Fe2 O3 @CC as the cathode is assembled, which displays high specific capacitance (343.2 mF cm −2 ) at 1 mA cm −2, energy density (93.43 µWh cm −2 ), and power density (700.7 µW cm −2 ) with the capacitance retention of 81.8% at 20 mA cm −2 after 5000 cycles, proving the feasibility for flexible wearable energy storage device.